Like scales from their eyes : visionary experience in Western Europe from Augustine to the eighth century - Moreira, Isabel (1992)
Vision narratives provide important evidence for the social and religious concerns of the society which records them, and are important sources for the mentalité of the period in which they are produced. This thesis provides an historical study of dream and vision narratives from the fourth to eighth centuries, with the hagiographic literature of Gaul and Merovingian Francia as its primary focus. During the period under review, there were important changes in the church's attitude towards the visionary experience. Whereas the fear of heterodoxy led early church Fathers to limit the spiritual authority of visions, by the sixth century in Gaul, dream and vision accounts were an important means by which churchmen could promote monastic and clerical ideals and their spiritual authority. Vision accounts were an important tool in the pastoral concerns of the clergy, enabling them to resolve or perpetuate disputes, smooth the process of Christianization, and provide imaged evidence of Christian doctrine. Dreams and visions confirmed the praesentia of saints at their tombs and at the site of their relics, and confirmed the role of the episcopate as their guardians and representatives. These issues are examined with special reference to the writings of Gregory of Tours in the sixth century. The effectiveness with which visions framed the deeds of the saints and conveyed impressions of spirituality is also examined over a broad sampling of Gallic and Merovingian hagiographic texts. The final chapter offers two case studies: the visionary experiences of St. Radegund of Poitiers, and St. Aldegund of Maubeuge.